2020
DOI: 10.1177/0734242x20919488
|View full text |Cite
|
Sign up to set email alerts
|

Alternative strategies towards a sustainable municipal solid waste management system: A case study in Cairo

Abstract: Major cities in transitional and developing countries are facing the ever-growing challenge of managing solid waste in a sustainable manner. While a variety of treatments exist for solid waste, cities are in need of a sustainable integrated municipal solid waste management (MSWM) system. Such a system is meant to assist them in selecting and investing in an appropriate combination of treatments for the waste they generate, depending on the composition and quantity of this waste. This study presents a systems a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The efficiency of integrated waste management systems has variously been evaluated using different methodologies. Investigations have suggested that the concept is good and hence its application in the developed world [19]. It is estimated that when utilized, between 75 and 90% of municipal waste in the United States of America could be eliminated.…”
Section: Proposed Waste Collection Modelmentioning
confidence: 99%
“…The efficiency of integrated waste management systems has variously been evaluated using different methodologies. Investigations have suggested that the concept is good and hence its application in the developed world [19]. It is estimated that when utilized, between 75 and 90% of municipal waste in the United States of America could be eliminated.…”
Section: Proposed Waste Collection Modelmentioning
confidence: 99%
“…Policymakers, local and national governments, construction industry practitioners, and academics dealing with the challenges of solid wastes in the MENA area were likely to benefit from the findings of this study. ElSaid and Aghezzaf [33] performed a system analysis of MSW management in Cairo, Egypt. To describe an underlying model of the MSW management system, a restricted non-linear mathematical model was developed for six waste material flows (glass, cardboard and paper, metals, plastics, organic material, and others).…”
Section: Introductionmentioning
confidence: 99%
“…Scientific literature reports research on the topic, especially initiatives reporting how municipal solid waste should be managed [5], frequent problems related to recycling and recovery [6], sustainability of smart waste management plans [7], the direction of research on waste recycling modeling [8], technologies for solid waste management [9]. especially those applied in developing countries [10] and the odd case study with some encouraging results such as the one reported in Egypt [11]. It is also important a general and systematic description of the scientific literature related to solid waste; in this regard, the literature reports studies such as the one conducted by C. Rodrigues-Vaz, D. Oliveira-Inomata, and J. Cesar-Stiirmer who after doing bibliometric research in Higher Education institutions, resorted to databases such as Web of Science, Scopus and Science direct, finding that out of a total of 118 articles only 14 were related to the topic [12].…”
Section: Introductionmentioning
confidence: 99%